False aneurysm of the interosseous artery and anterior interosseous syndrome - an unusual complication of penetrating injury of the forearm: a case report - Garavaglia Guido; Lucchina Stefano; Pini Ramon; Fusetti Cesare (Journal of Orthopaedic Surgery and Research, 2009)
Abstract Background Palsies involving the anterior interosseous nerve (AIN) comprise less than 1% of all upper extremity nerve palsies. Objectives This case highlights the potential vascular and neurological hazards of minimal penetrating injury of the proximal forearm and emphasizes the phenomenon of delayed presentation of vascular injuries following seemingly obscure penetrating wounds. Case Report We report a case of a 22-year-old male admitted for a minimal penetrating trauma of the proximal forearm that, some days later, developed an anterior interosseous syndrome. A Duplex study performed immediately after the trauma was normal. Further radiologic investigations i.e. a computer-tomographic-angiography (CTA) revealed a false aneurysm of the proximal portion of the interosseous artery (IA). Endovascular management was proposed but a spontaneous rupture dictated surgical revision with simple excision. Complete neurological recovery was documented at 4 months postoperatively. Conclusions/Summary After every penetrating injury of the proximal forearm we propose routinely a detailed neurological and vascular status and a CTA if Duplex evaluation is negative.